SOCIAL VALUES IN FUNERARY CEREMONY RESEARCH ON LINTAU BUO COMMUNITY, TANAH DATAR REGENCY - Putri, Siska Elasta (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This research aimed at studying social values in conducting a funerary ceremony which was held by Lintau Buo community. This funerary ceremony is a customary rite that must be held by the community. It is due to the status of this ceremony as the main customs (adat nan teradat). A qualitative method with an ethnography approach was used in conducting this research. The result showed that the social values in the funerary ceremony were mutual help, solidarity, kinship, reciprocity, communication, harmony, and concern.┬á